2010
DOI: 10.1038/ijir.2010.11
|View full text |Cite
|
Sign up to set email alerts
|

Insight on pathogenesis of lifelong premature ejaculation: inverse relationship between lifelong premature ejaculation and obesity

Abstract: Although both biological and psychological factors are important in the etiology, the exact pathogenesis of lifelong premature ejaculation (PE) remains to be clarified. Obesity is a worldwide epidemic that contributes to many chronic diseases. Obesity is associated with erectile dysfunction, but the relationship between obesity and PE has not yet been specifically investigated. The aim of this study was to evaluate the relationships of these two conditions. Between January 2008 and December 2009, we evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…This finding can be seen in line with Reas et al (2007) who demonstrated that accelerated weight gain occurs mainly during younger adulthood as it represents a critical time period due to ensuant lifestyle changes involving energy expenditure, dietary intake and they inaccurately assume their weight falls into a normal weight range [26] . Finally, the current results affirmed [17,27] .…”
Section: Discussionsupporting
confidence: 72%
“…This finding can be seen in line with Reas et al (2007) who demonstrated that accelerated weight gain occurs mainly during younger adulthood as it represents a critical time period due to ensuant lifestyle changes involving energy expenditure, dietary intake and they inaccurately assume their weight falls into a normal weight range [26] . Finally, the current results affirmed [17,27] .…”
Section: Discussionsupporting
confidence: 72%
“…In their study evaluating 236 MetS patients and 567 controls, Corona et al [ 63 ] reported a higher prevalence of PE among MetS patients (22.7% vs. 3% controls). On the contrary, Gökçe and Ekmekcioglu [ 64 ] reported that PE patients were leaner than healthy controls, and that the number of PE patients decreased as BMI increased. Amato et al [ 65 ] developed a new sex-specific metabolic index, the visceral adiposity index (VAI), which is calculated from WC, BMI, TG, and high-density lipoprotein values.…”
Section: Obesity and Metabolic Syndromementioning
confidence: 99%
“…The authors of that study also suggested that VAI is a useful index for assessing and calculating the risk of PE, and the relationship between adiposity and PE may be due to the increase in peripheral aromatization of androgens. The difference in the prevalence of PE in patients with MetS in the last two studies [ 64 66 ] may be due to regional and cultural differences. The differing prevalence of PE in patients with MetS may be due to the use of different definitions of PE, variations in the number of patients in each study, and the large inconsistency in the prevalence of hyperglycemia in these studies.…”
Section: Obesity and Metabolic Syndromementioning
confidence: 99%
“…However, it has not yet been settled the degree of interrelation between erectile dysfunction and premature ejaculation ( 26 ). To further stimulate the discussion, premature ejaculation was reported to have an inverse relationship with obesity ( 27 ). These findings highlight the complex relationship between sexual and metabolic disorders.…”
Section: Obesity and The Mechanical Dysfunctions That Hamper Sexual Amentioning
confidence: 99%